MiR-92b as a marker for TPF induced chemotherapy response prediction and prognosis evaluation in with advanced oral squamous cell carcinoma patients - Wen, Jianqiong; Xu, Houyi; Liu, Renying; Chen, Qiaoxiu; Dai, Yinhua; Xu, Yong (Cellular and Molecular Biology, 2020)
This study aimed to explore the clinical value of miR-92b in advanced oral squamous cell carcinoma (OSCC) and to observe the relationship between miR-92b and TPF induced chemotherapy and prognosis. Totally 114 patients with advanced OSCC admitted to our hospital were selected as the study subjects, all of whom received docetaxel, cisplatin and 5-fluorouracil (TPF) induction chemotherapy. In addition, another 80 healthy subjects who underwent physical examination in our hospital from the same period were enrolled. The serum expression of miR-92b was detected by qRT-PCR. Serum miR-92b was up-regulated in patients with advanced OSCC, and its expression was associated with higher TNM staging and lymph node metastasis. The receiver operating characteristic (ROC) curve revealed that the area under the curve (AUC) of serum miR-92b for the diagnosis of advanced OSCC was 0.931. After treatment, the miR-92b expression was significantly reduced, and the ROC curve showed an AUC value of 0.889 for predicting treatment sensitivity of serum miR-92b. What’s more, Logistic indicated that TNM staging, lymph node metastasis and serum miR-92b expression were independent risk factors affecting the treatment efficacy. Survival analysis demonstrated that OSCC patients with high miR-92b expression had poorer OS and DFS compared to patients with low miR-92b expression. Multivariate Cox regression exhibited that TNM staging, lymph node metastasis, and serum miR-92b expression were self-regulating risk factors for overall survival (OS) and disease-free survival (DFS) in patients with advanced OSCC. MiR-92b is up-regulated in patients with advanced OSCC, which can be used as a marker for induction chemotherapy and prognosis evaluation of advanced OSCC.